Effects of cassava juice on corrosion of mild and high yield steel bars in concrete structures (2009)
Nigeria is the highest producer of cassava in the world and cassava juice is rich in hydrocynic acid, a by-product from the extraction process. This paper examines the effect of cyanide ions, the reacting ions from hydrocyanic acid on reinforcing bars when cassava tubers are processed on reinforced concrete palteforms. Mild and high yield steel reinforcing bars are embedded in concrete cubes cast and cure for 21 and 28 days. These steel bars were used to model the experiment. Half-cell potential apparatus was used to take potentials measurement of both steel bars with concrete cubes immersed in hydrocyanic acid and ordinary water for 32 days. Corrosion rates under these different conditions were monitored. The results demostrated that both steel types will corrode in hydrocynaic acid, however, high yiled steel has better corrosion resistance than mild steel: this is due to the mechanical properites and chemical composition of the steel. It was also observed that with increase in curing age the degree of probability of corrosion decreased.